2018
DOI: 10.5099/aj180200072
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Level of Adiponectin and Macroscopic Changes of Placentae in Preeclampsia

Abstract: The objective of the present study was to measure the serum level of adiponectin in preeclamptic Egyptian pregnant women and find the possible correlations of maternal adiponectin level to measured insulin resistance in such case and to macroscopic features of placentae included in this study.The study population consisted of 30 preeclamptic patients and 30 matched healthy pregnant women during the third trimester.The results revealed that preeclamptic women were more insulin resistant with a significant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Other adipocyte products such as adiponectin, and interleukin-10 exert an antiatherogenic effect [45] . The results of our previous study revealed that preeclamptic women were more insulin resistant with a significant decrease in adiponectin level compared with healthy controls [46] . This was also in accordance with published data showing that body mass index is only related to visfatin in men, but not in women [47] .…”
Section: Discussionmentioning
confidence: 84%
“…Other adipocyte products such as adiponectin, and interleukin-10 exert an antiatherogenic effect [45] . The results of our previous study revealed that preeclamptic women were more insulin resistant with a significant decrease in adiponectin level compared with healthy controls [46] . This was also in accordance with published data showing that body mass index is only related to visfatin in men, but not in women [47] .…”
Section: Discussionmentioning
confidence: 84%
“…Taken together with the current demonstration that women with recent GDM have low adiponectin at both 1- and 3-years after delivery, these data collectively suggest that hypoadiponectinemia is a chronic feature of this patient population before, during, and after pregnancy. Moreover, a higher leptin/adiponectin ratio in women with GDM has been associated with an unfavourable cardiovascular risk factor profile on postpartum follow-up [ 28 ] and hypoadiponectinemia in pregnancy has been suggested as a possible factor contributing to preeclampsia, which is also associated with future risk of CVD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%